2003
DOI: 10.2134/jeq2003.2200
|View full text |Cite
|
Sign up to set email alerts
|

Size Distribution of Organic Matter and Associated Propiconazole in Agricultural Runoff Material

Abstract: Sorption and desorption characteristics of propiconazole (1-[[2-(2,4-dichlorophenyl)-4-propyl-1,3-dioxolan-2-yl]methyl]-1H-1,2,4-triazole) to different particle/aggregate-size fractions of agricultural runoff material were investigated. Emphasis was put on clay and colloidal size fractions to evaluate their role as potential sorbents and carriers for this pesticide. The runoff material was separated into size fractions ranging from 2 mm to ca. 15 nm by wet sieving, sedimentation, centrifugation, and membrane u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Jamet and Eudeline (1992) compared the mobility of 17 triazole fungicides in a silt loam soil and concluded that their mobility was inversely related to their octanol/water partition coefficient. Wu et al (2003) investigated the sorption and desorption characteristics of propiconazole to different particle/aggregate-size fractions of agricultural runoff material and showed that sorption increased with decreasing particle size.…”
Section: Introductionmentioning
confidence: 99%
“…Jamet and Eudeline (1992) compared the mobility of 17 triazole fungicides in a silt loam soil and concluded that their mobility was inversely related to their octanol/water partition coefficient. Wu et al (2003) investigated the sorption and desorption characteristics of propiconazole to different particle/aggregate-size fractions of agricultural runoff material and showed that sorption increased with decreasing particle size.…”
Section: Introductionmentioning
confidence: 99%
“…This might be due to the difference in surface area between the two fractions of suspended solids and strong hysteresis. 14,20) As shown in Figs. 3b, c, g and h, the concentrations of esprocarb in suspended solids were higher than those of other pesticides, and thiobencarb was detected in relatively higher concentrations in SS 0.5 at the Iinuma river site, and dimethametryn in SS 1.0 at Fureaibashi.…”
Section: Pesticides In Suspended Solidsmentioning
confidence: 82%
“…In the depositional runoff sediment, the fraction S1 (0.16–2.0 μm) and S2 (0.03–0.16 μm) accounted for only 7.5 and 0.8% of the total sample mass, and the coarser fractions (>2 μm) made up more than 90%. In runoff water collected at the edge of agricultural fields, however, these two size fractions (S1 + S2) have been found to make up 80% of the total sediment mass and, thereby, represent a major part of solid material suspended in water [18].…”
Section: Resultsmentioning
confidence: 99%
“…When entering the watercourse, the concentration of suspended sediment generally is diluted, and a large fraction of propiconazole originally sorbed to sediment surfaces might desorb. For some soils, propiconazole showed strong hysteresis [18]. In that case, the desorption kinetic is rather slow and, consequently, the proportion of particle‐bound propiconazole will be higher under desorption than the one calculated from the sorption coefficient.…”
Section: Resultsmentioning
confidence: 99%